Evaluating the Impact of Penile Girth Discrepancy on Patient Bother in Men with Peyronie's Disease: An Observational Study. Issue 8 (20th June 2020) - Salter, Carolyn A.; Nascimento, Bruno; Terrier, Jean-Etienne; Taniguchi, Hisanori; Bernie, Helen; Miranda, Eduardo; Jenkins, Lawrence; Schofield, Elizabeth; Mulhall, John P.
Abstract: Background: Men with Peyronie's disease (PD) may experience penile narrowing. Little data on penile girth changes and their psychosocial impact exist. Aim: To assess girth discrepancy in men with PD and its association with patient bother. Methods: This was a retrospective observational study. All patients with PD at our institution who were seen in the sexual medicine clinic and who completed 3 validated instruments the PD questionnaire (PDQ), Self-Esteem and Relationship (SEAR) questionnaire, and a depression questionnaire, the Center for Epidemiologic Studies Depression Scale (CES-D), and a curvature assessment were included. Patient and PD characteristics are described. Associations of instability and bother to girth differences are assessed. 2 outcomes for girth differences are classified as (i) girth difference of ≥ 1 cm vs less and (ii) girth differences of ≥10% vs less. Unadjusted and adjusted effects of PD and patient characteristics are assessed on the outcome of high bother using logistic regression models. Outcomes: The main outcomes of this study were penile girth changes, instability, and questionnaire scores. High bother was defined as a PDQ bother score of ≥9. Results: A total of131 men had midshaft curvature and were the focus of the study. Their mean age was 59 ± 9 (range 31–78) years. PD duration was 16 ± 25 (range 1–180) months, with a mean degree of primary curvature of 37 ± 20 o . Mean girth difference between base and point of maximum curvature was 0.78 ± 0.53 cm equating to a mean girth difference at point of maximum curvature of 6 ± 4%. Instability was present in 53% of men. There were 54 men with a girth difference of ≥ 1 cm and 23 men with a ≥10% change in girth. There was no difference in CES-D, SEAR, or PDQ domain scores or high bother in men with significant girth changes. Univariable analysis of predictors of high bother included the degree of curvature (odds ratio [OR]: 1.06; P < .001), instability (OR 6.62; P < .001), CES-D sum (OR 1.09; P = .002), and SEAR score (OR 0.96; P = .001). On multivariate analysis, only the degree of primary curvature was predictive of high bother (OR 1.06; P < .001). Clinical Implications: Penile girth changes have little impact on overall psychosocial well-being. The degree of penile curvature is the primary predictor of patient bother. Strengths and Limitations: Strengths include a large patient population and use of validated questionnaires. Limitations include single-center, retrospective study and subjective instability grading. Conclusions: Penile girth discrepancy in men with PD has limited psychosocial impact. Clinically significant bother was associated with the degree of primary curvature.